In silico identification of AMPylating enzymes and study of their divergent evolution - Khater, Shradha (Sci Rep, 2015)
AMPylation is a novel post-translational modification (PTM) involving covalent attachment of an AMP moiety to threonine/tyrosine side chains of a protein. AMPylating enzymes belonging to three different families, namely Fic/Doc, GS-ATase and DrrA have been experimentally characterized. Involvement of these novel enzymes in a myriad of biological processes makes them interesting candidates for genome-wide search. We have used SVM and HMM to develop a computational protocol for identification of AMPylation domains and their classification into various functional subfamilies catalyzing AMPylation, deAMPylation, phosphorylation and phosphocholine transfer. Our analysis has not only identified novel PTM catalyzing enzymes among unannotated proteins, but has also revealed how this novel enzyme family has evolved to generate functional diversity by subtle changes in sequence/structures of the proteins. Phylogenetic analysis of Fic/Doc has revealed three new isofunctional subfamilies, thus adding to their functional divergence. Also, frequent occurrence of Fic/Doc proteins on highly mobile and unstable genomic islands indicated their evolution via extensive horizontal gene transfers. On the other hand phylogenetic analyses indicate lateral evolution of GS-ATase family and an early duplication event responsible for AMPylation and deAMPylation activity of GS-ATase. Our analysis also reveals molecular basis of substrate specificity of DrrA proteins.